The genus Sofiella gen. nov. (Hemiptera, Cicadellidae, Cicadellini) with description of two new species from Brazil - Domahovski, Alexandre Cruz; Alasmar, Luísa; Cavichioli, Rodney Ramiro (Zootaxa, 2023)
The Neotropical sharpshooter Sofiella gen. nov. is described and illustrated from the Araucaria moist forest in Southern and Southeastern Brazil (States of Paraná, Rio Grande do Sul and São Paulo) based on two new species, S. takiyae sp. nov. (type-species) and S. nicolasi sp. nov. The new genus shares features with Exogonia but can be differentiated by the pronotal width slightly narrower than the transocular width of the head; pygofer without setose processes; aedeagus bearing a pair of apical processes; female sternite VII with posterior margin convex; and second valvula with few long, not prominent teeth and a well developed preapical prominence.